Fetal Immune Response to Chorioamnionitis - Kallapur, Suhas G.; Presicce, Pietro; Rueda, Cesar M.; Jobe, Alan H.; Chougnet, Claire A. (Seminars in Reproductive Medicine, 2014)
Chorioamnionitis is a frequent cause of preterm birth and is associated with an increased risk for injury responses in the lung, gastrointestinal tract, brain, and other fetal organs. Chorioamnionitis is a polymicrobial nontraditional infectious disease because the organisms causing chorioamnionitis are generally of low virulence and colonize the amniotic fluid often for extended periods, and the host (mother and the fetus) does not have typical infection-related symptoms such as fever. In this review, we discuss the effects of chorioamnionitis in experimental animal models that mimic the human disease. Our focus is on the immune changes in multiple fetal organs and the pathogenesis of chorioamnionitis-induced injury in different fetal compartments. As chorioamnionitis disproportionately affects preterm infants, we discuss the relevant developmental context for the immune system. We also provide a clinical context for the fetal responses.
Keywords: infection; fetal inflammatory response; prematurity; animal models